2020
DOI: 10.3389/fneur.2020.575376
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Analysis of the Cerebrovascular Thrombi Proteome in Human Ischemic Stroke: An Exploratory Study

Abstract: Objective: Mechanical retrieval of thrombotic material from acute ischemic stroke patients provides a unique entry point for translational research investigations. Here, we resolved the proteomes of cardioembolic and atherothrombotic cerebrovascular human thrombi and applied an artificial intelligence routine to examine protein signatures between the two selected groups. Methods: We specifically used n = 32 cardioembolic and n = 28 atherothrombotic diagnosed thrombi from patients suffering from acute stroke an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
5
14
1
Order By: Relevance
“…We successfully analyzed the proteome of FFPE samples in the current study, identifying 1,581 protein groups as part of the proteome of AIS thrombi using LC-MS/MS. Our results are in line with previous studies performed on FF samples, such as the study of Dargazanli et al who identified 2,455 proteins in 50 samples ( 31 ) and the earlier study by Munoz et al, which used four samples and identified a proteome in the order of 1,600 proteins ( 32 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We successfully analyzed the proteome of FFPE samples in the current study, identifying 1,581 protein groups as part of the proteome of AIS thrombi using LC-MS/MS. Our results are in line with previous studies performed on FF samples, such as the study of Dargazanli et al who identified 2,455 proteins in 50 samples ( 31 ) and the earlier study by Munoz et al, which used four samples and identified a proteome in the order of 1,600 proteins ( 32 ).…”
Section: Discussionsupporting
confidence: 93%
“…Both of these earlier studies found a set of proteins of interest helpful to advance AIS thrombus proteome characterization ( 31 , 32 ). We acknowledge that our use of FFPE samples allowed us to identify less proteins than previous studies which used FF samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous proteomic study found that two inflammation proteins (integrin alpha-M and mitochondrial superoxide dismutase) are associated with high blood low-density lipoprotein (LDL) [10]. In another study, these two proteins failed to differentiate between cardioembolic vs. atherosclerotic etiology [11]. Also, another study analyzed four thrombi, with 1,600 proteins identified [12].…”
Section: Discussionmentioning
confidence: 98%
“…120 Finally, higher IL-1β expression was measured in LAA thrombi, 112 while coagulation factor XIII was associated with CE. 115 Some studies aimed to compare the features of CRY thrombi with those of known TOAST etiology. Most of them found similar proportions of RBCs, 39,57,64,96,122-124,127 FBR, PLTs (or both together), 57,76,96,[122][123][124]127 and WBCs between CRY and CE thrombi.…”
Section: Relationship Between Thrombus Features and Stroke Etiologymentioning
confidence: 99%